MANAJEMEN DAKWAH TAREKAT QADIRIYAH NAQSABANDIYAH DI DESA BUMI KENCANA KECAMATAN SEPUTIH AGUNG KABUPATEN LAMPUNG TENGAH - Anggraini, Vira Shanty; Santoso, Boby Rachman (Universitas Islam Negeri Raden Intan Lampung, 2022)
One of the Islamic da’wah organizations is the tarekat which is alleged to have existed since Islam entered the archipelago. Tarekat generally teach sufism to their followers. The Qadiriyah Naqsabandiyah order is one of the tarekat in Indonesia that has many followers. Examining more deeply the management used in the Qadriya Naqsabandiyah order is something very interesting. This study uses a qualitative method with a socio-phenomenological approach whose data were obtained through observations, interviews and documentation at the Qadiriyah Naqsabandiyah institute in Bumi Kencana village, Seputih Agung district, Central Lampung district. The results showed that the da’wah management applied in the Qadiriyah Naqsabandiyah congregation through several activities, including, turban, remembrance and ‘‘ubûdiyah together (tawajahun), holding quarterly remembrance, and studying classical books. The impact on people who study the teachings of this tarekat is that they begin to be enthusiastic in carrying out the teachings recommended in Islam develop a positive side in socializing and can manage their time to set aside their worldly activities in order to get closer to Allah SWT.